KONTRIBUSI KECEPATAN, KOORDINASI MATA TANGAN DAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLING PADA ATLET BOLA BASKET KABUPATEN KERINCI - Cundra Bahar (Ensiklopedia of Journal, 2019)
Based on the observations made on the athletes, Basketball Kerinci shows that dribbling skills possessed basketball athletes’ Kerinci district are still low. The ability of the athletes’ dribbling basketball Kerinci district are influenced by many factors, and three of them were allegedly affected by speed, hand-eyes coordination, and agility. This study aims to clarify the relationship and the contribution of speed, hand-eyes coordination and agility of the athletes’ basketball dribbling skills Kerinci district, individually or jointly. The population in this study is all athletes basketball Kerinci district in 2015-2016 totaling 30 people. The sampling technique is done by total sampling, the number of samples used as many as 30 people. Data were collected using an instrument run 20 meters for measuring speed, throwing a ball catch for measuring hand-eyes coordination, running back and forth (shuttle run) to measure agility and to measure the ability of dribbling basketballs used zigzag run. The result showed that: (1) the speed has a positive relationship with t = 2.76> t table = 1.701 and accounted for 21.41% of the dribbling skills. (2) hand-eye coordination have a positive relationship with t = 2.44> t table = 1.701 and accounted for 17.48% of the dribbling skills. (3) eye-hand coordination has a positive relationship with t = 2.68> t table = 1.701 and accounted for 20.36% of the dribbling skills. (4) speed, eye-hand coordination and agility has a positive relationship with F counted (6.68)> F table (2.98) and contributed jointly by 18.96% against the dribbling skills